2013
DOI: 10.1002/jssc.201201109
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation into the effects of ordered particle packing and slip flow on the performance of chromatography

Abstract: The pressure drop and the plate height of chromatography columns packed with particles in the face-centered cubic, the body-centered cubic and the simple cubic configurations are calculated by a volume averaging method model. It is found that the Kozeny-Carman equation provides a reasonable prediction of the pressure drop when particles are in the face-centered cubic configuration, but overestimates the pressure drop when particles are in the body-centered cubic and the simple cubic configurations. The face-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…For the case of the protein bovine serum albumen, this ratio is 1.5 %. They concluded with agreement with the results of Yan and Wang 77 that extraordinary values of h are possible even without slip flow, that flow rate is enhanced by slip flow and that use of particle diameters tailored to the analyte diameter might give a lower h by excluding analyte from stagnant regions.…”
Section: Small Particles In Capillary Column Formatsupporting
confidence: 82%
“…For the case of the protein bovine serum albumen, this ratio is 1.5 %. They concluded with agreement with the results of Yan and Wang 77 that extraordinary values of h are possible even without slip flow, that flow rate is enhanced by slip flow and that use of particle diameters tailored to the analyte diameter might give a lower h by excluding analyte from stagnant regions.…”
Section: Small Particles In Capillary Column Formatsupporting
confidence: 82%
“…However, simulations of slip flow in packed beds with colloidal silica particles predicted a much reduced flow enhancement than the experimental results described above [166, 167]. While the theory underlying slip flow in open capillaries is understood, the theory behind slip flow in packed beds has recently been investigated.…”
Section: Emerging Chromatographic Technologiesmentioning
confidence: 99%
“…As such the discrepancy between the experimental and simulated results is not definitively understood as yet. That said, simulations of flow moving through the packed bed indicated that regions of stagnant flow exist where the fluid stream makes contact with the particles indicating that tortuosity may affect the flow velocity profile in slip flow chromatography thereby reducing the flow enhancement [166, 167]. …”
Section: Emerging Chromatographic Technologiesmentioning
confidence: 99%
“…Most theoretical and experimental works addressing solute transport in porous media have focused on porous media comprising impermeable particles, pillars or monoliths [4,[13][14][15][16][17][18][19][20]. Perhaps due to their complex pore geometry, experimental and theoretical predictions of solute transport in hierarchical porous media are few.…”
Section: Introductionmentioning
confidence: 98%